flex & bison - Levine, John R. (O'Reilly Media, 2011)
flex & bison covers the same core functionality vital to Linux and Unix program development, along with several important new topics. You'll find revised tutorials for novices and references for advanced users, as well as an explanation of each utility's basic usage and simple, standalone applications you can create with them. With flex & bison, you'll discover the wide range of uses these flexible tools offer.